2013
DOI: 10.1177/1352458513501570
|View full text |Cite
|
Sign up to set email alerts
|

Comparing long-term results of PASAT and SDMT scores in relation to neuropsychological testing in multiple sclerosis

Abstract: As a single assessment tool for cognition in MS, the SDMT is more valid and reliable compared to PASAT3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
47
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(56 citation statements)
references
References 32 publications
(59 reference statements)
5
47
0
4
Order By: Relevance
“…Boringa et al [12] provided normative values for the SDMT in a Dutch healthy population, which have been used ever since for many neuropsychological and natural history studies [9,12,15,16,24]. Although they found an influence of age, gender and education, they did not account for any of the reported effects, which potentially lead to an underestimation of cognitive dysfunction in earlier publications.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Boringa et al [12] provided normative values for the SDMT in a Dutch healthy population, which have been used ever since for many neuropsychological and natural history studies [9,12,15,16,24]. Although they found an influence of age, gender and education, they did not account for any of the reported effects, which potentially lead to an underestimation of cognitive dysfunction in earlier publications.…”
Section: Discussionmentioning
confidence: 80%
“…In previous studies, abnormal test performance was defined by comparing an examinee's result to the average performance of the most suitable normative (sub)group, taking no account of any potential demographic influence [9,12,15,24]. Parmenter et al [10] were the first authors to provide regression-based norms for the SDMT with the potential to resolve this limitation and found higher rates of impairment than previously published discrete norms, which was confirmed later by Berrigan et al [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We did not examine alternative neuropsychological measures in the current study; however, other researchers have made comparisons between the Symbol Digit Modalities Test (SDMT) and the PASAT to classify cognitive impairment in MS (Brochet et al, 2008;Drake et al, 2010;Sonder, Burggraaff, Knol, Polman, & Uitdehaag, 2014). Specifically, these researchers have suggested that the SDMT supplement (Brochet et al, 2008) or even replace the PASAT in the MS Functional Composite (Drake et al, 2010).…”
Section: Discussionmentioning
confidence: 86%
“…8 Enter exercise, an intervention that is both complied with and relatively free of side effects, and the data indicate some notable gains in memory and attention. It is, however, surprising that no improvements were seen on the Symbol-Digit Modality Test, considered the most sensitive marker of information processing speed, the quintessential cognitive abnormality in MS. 9 While this highlights the need for the data to be replicated, the findings do overlap broadly with those found in other disease groups and in healthy subjects, as the authors note, and where intriguing neuroimaging results enhance the validity of exercise as an effective treatment for cognitive dysfunction.…”
mentioning
confidence: 80%